Analysis of ACE2 and TMPRSS2 coding variants as a risk factor for SARS‐CoV‐2 from 946 whole‐exome sequencing data in the Turkish population. Issue 11 (22nd July 2022) - Duman, Nilgun; Tuncel, Gulten; Bisgin, Atil; Bozdogan, Sevcan Tug; Sag, Sebnem Ozemri; Gul, Seref; Kiraz, Aslihan; Balta, Burhan; Erdogan, Murat; Uyanik, Bulent; Canbek, Sezin; Ata, Pinar; et al.
Abstract: Heterogeneity in symptoms associated with COVID‐19 in infected patients remains unclear. ACE2 and TMPRSS2 gene variants are considered possible risk factors for COVID‐19. In this study, a retrospective comparative genome analysis of the ACE2 and TMPRSS2 variants from 946 whole‐exome sequencing data was conducted. Allele frequencies of all variants were calculated and filtered to remove variants with allele frequencies lower than 0.003 and to prioritize functional coding variants. The majority of detected variants were intronic, only two ACE2 and three TMPRSS2 nonsynonymous variants were detected in the analyzed cohort. The main ACE2 variants that putatively have a protective or susceptibility effect on SARS‐CoV‐2 have not yet been determined in the Turkish population. The Turkish genetic makeup likely lacks any ACE2 variant that increases susceptibility to SARS‐CoV‐2 infection. TMPRSS2 rs75603675 and rs12329760 variants that were previously defined as common variants that have different allele frequencies among populations and may have a role in SARS‐CoV‐2 attachment to host cells were determined in the population. Overall, these data will contribute to the formation of a national variation database and may also contribute to further studies of ACE2 and TMPRSS2 in the Turkish population and differences in SARS‐CoV‐2 infection among other populations.